Retrato e autorretrato em sala de aula : construção da consciência de si e do outro - Rita, Dora Iva, 1954- (2018)
Activities associated to portrait and self-portrait seems to lead students to find their own personal means for structuring and restruc¬turing themselves. To study and to understand these interaction mechanisms are relevant to the enrichment of the school work and to promote self-esteem, acceptance and respect for others, which will help prevent academic failure and early school dropping